Sonographic evaluation of the endochondral ossification process of the thyroid cartilage in children. Issue 2 (9th October 2017) - Yildiz, Adalet Elcin; Sahap, Seda Kaynak; Elhan, Atilla Halil; Fitoz, Suat
Abstract: Purpose: To determine the sonographic appearances of the endochondral ossification process of the thyroid cartilage in children. Methods: Thyroid cartilage sonography (US) of 420 children was performed with a high‐resolution linear‐array transducer. Right and left laminae of the thyroid cartilage, including the inferior horns, were examined. Ossification foci were evaluated for their presence, location, shape, size, echo pattern, and number. Results: Four hundred nineteen children, 239 girls and 180 boys, were enrolled in the study with a mean age of 109.8 ± 60.7 months. Ossification foci were found in 167 children (39.9%). First ossification focus detection age was 72 months in girls and 79 months in boys. On both laminae, the most frequent appearance of the ossification focus was hypoechoic (right: 94.8%, left: 93.5%). Prevalence and number of ossification foci increased with age in each sex. The shape of the ossification foci in both laminae was generally nonexpansile (right: 92.9%, left: 93.5%). Conclusion: Endochondral ossification process of the thyroid cartilage begins in the first decade with extracellular matrix changes, which can be detected as hypoechoic foci by US. These foci can be expansile, and radiologists should be aware of this entity to avoid misdiagnosing them as abnormal masses.